Analisis Perhitungan Upah Lembur Karyawan Kontrak Pada PT SLJ Global Tbk - -, Ristiyani - (EKONOMIA, 2019)
This company has been done the export to various countries. Since the company tries to achieve the production targets, the company often does overtime work and if demand is large, the company will operate on holidays. The aim of this research is to find out and analyze the suitability of work overtime wages for contract employees at PT SLJ Global Tbk to the Decree of the Minister of Manpower No:KEP.102/MEN/VI/2004. The method used is a comparative method which is comparing the calculation of contract employee work overtime wages of PT SLJ Global Tbk with the calculation of work overtime wages based on the Minister of Manpower Decree No: KEP.102/MEN/VI/2004 on article 11 which contains the calculation of work overtime wages. Calculation of work overtime wages for contract employees experienced a difference of underpayment of 91.28% and testing of hypotheses, the hypothesis was accepted because the calculation of work overtime wages of contract employees was not in accordance with the Decree of the Minister of Manpower No: KEP.102/MEN/VI/2004. Based on the results of the study, it can be concluded that the calculation of work overtime wages of contract employees at PT SLJ Global Tbk does not reach the standards that have been applied by the Government which refers to the Minister of Manpower Decree No: KEP.102/MEN/VI/2004. The difference lies in multiplying hourly of work overtime wages. Seeing this situation, the company is suggested to provide fair and wise welfare to all employees.